A synthetic glycodendropeptide induces methylation changes on regulatory T cells linked to tolerant responses in anaphylactic-mice - Núñez, Rafael; Rodríguez, María J.; Lebrón-Martín, Clara; Martín-Astorga, María del Carmen; Ramos-Soriano, Javier; Rojo, Javier; Torres, María J.; Cañas, José A.; Mayorga, Cristobalina (Frontiers in Immunology, 2023)
Introduction: Lipid transfer proteins (LTPs) are allergens found in a wide range of plant-foods. Specifically, Pru p 3, the major allergen of peach, is commonly responsible for severe allergic reactions. The need for new alternatives to conventional food allergy treatments, like restrictive diets, suggests allergen immunotherapy as a promising option. It has been demonstrated that sublingual immunotherapy (SLIT) with synthetic glycodendropeptides, such as D1ManPrup3, containing mannose and Pru p 3 peptides induced tolerance in mice and that the persistence of this effect depends on treatment dose (2nM or 5nM). Moreover, it produces changes associated with differential gene expression and methylation profile of dendritic cells, as well as phenotypical changes in regulatory T cells (Treg). However, there are no works addressing the study of epigenetic changes in terms of methylation in the cell subsets that sustain tolerant responses, Treg. Therefore, in this work, DNA methylation changes in splenic-Treg from Pru p 3 anaphylactic mice were evaluated. Methods: It was performed by whole genome bisulphite sequencing comparing SLIT-D1ManPrup3 treated mice: tolerant (2nM D1ManPrup3), desensitized (5nM D1ManPrup3), and sensitized but not treated (antigen-only), with anaphylactic mice. Results: Most of the methylation changes were found in the gene promoters from both SLIT-treated groups, desensitized (1,580) and tolerant (1,576), followed by the antigen-only (1,151) group. Although tolerant and desensitized mice showed a similar number of methylation changes, only 445 genes were shared in both. Remarkably, interesting methylation changes were observed on the promoter regions of critical transcription factors for Treg function like Stat4, Stat5a, Stat5b, Foxp3, and Gata3. In fact, Foxp3 was observed exclusively as hypomethylated in tolerant group, whereas Gata3 was only hypomethylated in the desensitized mice. Discussion: In conclusion, diverse D1ManPrup3 doses induce different responses (tolerance or desensitization) in mice, which are reflected by differential methylation changes in Tregs.